The impact of banking Compliance in combating money laundering and terrorist financing: An applied research in a sample of Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of this research is to demonstrate the impact of banking compliance in combating money laundering and terrorist financing through banks. The phenomenon of money laundering and terrorist financing has received wide attention in the countries of the world and international organizations because of the negative effects this phenomenon has on the global economy as a result of exploiting developments and modern banking operations to pass Money laundering and terrorist financing operations in order to legitimize illegal funds and obliterate their criminal sources, which obliged the banking sector to increase control measures in order to reduce these operations, which conceal money laundering through the activation of Bodies, programs and mechanisms of control, including monitoring compliance in banks, which is one of the most important functions in the banking business to follow up and monitor the extent of banks' compliance with the control legislation in order to achieve its objectives, so the problem of this research is focused on the following question is there a role of the Compliance Controller in significantly reducing laundering operations Money and terrorist financing in banks? To clarify the relationship between the main and sub-research variables, a main hypothesis and two sub-hypotheses were formulated. The questionnaire was adopted as a tool in collecting data and information related to the research, which was distributed to the staff of the Compliance Controller and the staff of the Anti-Money Laundering and Terrorism Financing Section in the banks. Two government banks and three private banks, using descriptive and analytical method, as well as the use of multiple regression analysis to test the hypotheses of research, and presented a number of cases of money laundering and terrorist financing similar to or actually occurred in Iraqi banks. The most important of these results is the existence of a significant impact between the Compliance and Anti-Money Laundering and Combating Terrorist Financing in the public and private banks. Bodies in the bank to develop policies and mechanisms in the field of combating money laundering and terrorist financing.